Desenvolvimento de método para determinação multirresíduo de agrotóxicos em ovos empregando método QuEChERS e UHPLC-MS/MS - Loose, Roberta Fabricio (2020)
The egg is one of the most consumed foods in the world and it has a complex composition due to the amount of proteins, lipids, vitamins and minerals present in it, which makes it difficult to extract compounds from this matrix without interferents effect. In addition, in recent years, the misuse and indiscriminate use of pesticides has been evidenced by the results of residue determinations of these substances in food. This shows the need to develop suitable methods for the determination of pesticides in samples of high complexity. Thus, this study had as main objective the development and validation of a sample preparation method for the determination of pesticide residues in eggs using a modified QuEChERS method and UHPLC-MS/MS. This modification in the QuEChERS method was carried out basically in the extraction solvent, and in the clean-up step, where nine different tests were carried out to choose the best material for cleaning. The optimized method is basically composed of four stages, using as extraction solvent ACN 5% formic acid (v/v), MgSO4 and NaCl as partition salts, and the Captiva EMR-Lipid® cartridge for removing interferences in the clean-up step, for further dilution of the extracts in the mobile phase. The results of the validation showed that the method is linear in the range of 0.5 to 20 μg L-1, and 71 pesticides were determined. The results of the accuracy and precision tests, evaluated at levels 5, 50 and 100 μg kg-1 (n = 6), proved to be adequate, since they showed recoveries between 70 and 120%, with RSD ≤ 20%. The limits of quantification and detection of the method were 5 and 100 μg kg-1 and 1.5 and 30 μg kg-1, respectively. The method was applied in the analysis of 41 commercial egg samples from different cities and regions from Rio Grande do Sul and Paraná states, however, no pesticides were detected in these samples.